Parental Supervision In The Social Development Of Early Childhood In Kencana Mekar Kindergarten Bahbutong - Putri Dirgahayu Pasaribu; Alfin Siregar; Tiara Putri Mahisani; Suci Permata Hati; Wahyuni Dazura (Sean Institute, 2024)
This study aims to examine the influence of parental support on the social development of early childhood in Kencana Blossom Bahbutong Kindergarten. Parental support is one of the important factors in developing children's social skills, such as interacting with peers, recognizing emotions, and resolving conflicts. Using a descriptive qualitative method, data were collected through observations both at school and at home, interviews related to parental guidance, and documentation with participants consisting of 25 parents, 3 teachers, and the principal. The theories used are Erikson's social development theory, Epstein's parental involvement, and Bandura's social learning theory. The results of the study showed that intensive parental guidance has a positive impact on children's social interaction, adaptation, and cooperation skills in the school environment. Children who are actively assisted by parents have more developed social skills compared to children who receive less assistance. These findings reinforce the importance of parental involvement in early childhood education to support children's social development. Children who receive substantial assistance from parents show superior social skills compared to children who receive minimal support. These results demonstrate the important role of parents in actively assisting early childhood to ensure optimal social growth.